Ungedrucktes von Franz Kafka. Unpublished by Franz Kafka. An introduction (Materiali di Estetica. Terza serie, 2017)
This is the first translation of Brod’s text which was originally published on the weekly newspaper “Die Zeit” on 22.10.1965. This edition, compared with the one in “The Prague Circle” (1966), also presents a new translation of Kafka’s only known aesthetical fragment of 1906 upon the experience of beauty and novelty, two elements which play a salient role in the whole of his narrative. Brod’s suggestions as well as Kafka’s counterarguments encompass the process of knowledge thus developing peculiar points of view upon subjectivity and creative processes.KEYWORDS:  Aesthetics – Fiction – Creative Processes – Beauty – Novelty – Arguments vs Counterarguments; Intermediality; Intertextuality; Max Brod – Franz Kafka